A research agenda for global environmental politics - Dauvergne, Peter; Alger, Justin (Cheltenham, UK Northampton, MA, USA Edward Elgar Publishing, 2018)
"In a world confronted with escalating environmental crises, are academics asking the right questions and advocating the best solutions? This Research Agenda paves the way for new and established scholars in the field, identifying the significant gaps in research and emerging issues for future generations in global environmental politics. From an analysis of state and non-state environmental governance to the politics of climate change, food sustainability, forests and oceans, the preeminent academics and leading researchers take an important step in establishing an agenda for the future trajectory of research. Split into three sections - global environmental governance, the politics of environmental problems, and engaged research and scholar activism - chapters discuss the most influential steps in recent environmental and political studies and offer original perspectives on the future trends. Inspiring the next generation of academics and activists, this Research Agenda provides excellent guidance for graduate students and supervisors looking for the most innovative and pressing research questions in environmental politics."--Page 4 of cover.
1. Researching Global Environmental Politics: Trends, Gaps, and Emerging Issues / Justin Alger and Peter Dauvergne -- Part I: Global Environmental Governance. 2. Three Ways to Study the Global Politics of Trade and the Environment / J. Samuel Barkin -- 3. Green Finance / Susan Park -- 4. The Sustainable Development Goals in Global Environmental Politics / Erika Weinthal -- 5. Studying Institutions for Nonstate Environmental Governance / Lars H. Gulbrandsen -- 6. Extractives and Environmental Governance Research / Timothy Adivilah Balag'kutu, Jason J. McSparren, and Stacy D. VanDeveer -- Part II: The Politics of Environmental Problems. 7. The New Global Political Economy of Waste / Kate O'Neill -- 8. Researching the Global Environmental Politics of Food / Jennifer Clapp and Phoebe Stephens -- 9. Ocean Governance / Elizabeth R. DeSombre -- 10. 10. Not Just a Case Study: Strategies for Researching Climate Change Politics / Sonja Klinsky -- 11. Encountering Climate's New Governance / Harriet Bulkeley, Mark Cooper, and Johannes Stripple -- 12. Bringing the Environment Back In: Materiality in Climate Change Politics Research / Felicia Peck -- Part III: Engaged Research and Scholar Activism. 13. Does the Arc of History Bend Towards Climate Justice? Towards an Agenda for Engaged Research / J. Timmons Roberts -- 14. Global Environmental Politics Research in a Time of Crisis / Kate J. Neville and Matthew Hoffmann.
Includes bibliographical references and index.
Keywords: Environmental policy -- International cooperation